The factors related to teacher attitudes toward inclusive schools - Icha Kusumadewi; Eny Purwandary; Usmi Karyani (Konselor, 2022)
This study discusses factors related to teacher attitudes toward inclusive schools. The variables studied were self efficacy (X1) and understanding of children with special needs (X2) as an independent variables  then  teacher attitude to school of inclusion as a dependent variable (Y). Data processing methods in hypothesis testing using multiple regression statistical analysis with participants in this study were teachers from inclusive schools (N=500). The results of this study indicate that there is relationship between self-efication and understanding of children with special needs toward teacher attitude to school of inclusion (p <α; 0.000 <0.05), with the effect of a contribution of 0.93 (93%). Therefore, in this study Ho was rejected and Ha was accepted